Gamma-X mixing in GaAs-Ga(1-x)Al(x)As quantum wells under hydrostatic pressure (2008)
ABSTRACT: The mixing between the Γ and X conduction-band valleys in GaAs-Ga1−xAlxAs quantum wells is investigated by using a phenomenological model which takes into account the effects of applied hydrostatic pressure. The dependencies of the variationally calculated photoluminescence peak-energy transitions on the applied hydrostatic pressure and quantum-well width are presented. A systematic study of the Γ − X mixing parameter is also reported. In particular, it is shown that the inclusion of the Γ − X mixing explains the non-linear behavior in the photoluminescence peak of confined exciton states that has been experimentally observed for pressures above 15 kbar in GaAs-Ga1−xAlxAs quantum wells.